Endoscopic evaluation of food bolus formation and its relationship with the number of chewing cycles. (16th March 2015) - Fukatsu, H.; Nohara, K.; Kotani, Y.; Tanaka, N.; Matsuno, K.; Sakai, T.
Summary It is known that solid food is transported to the pharynx actively in parallel to it being crushed by chewing and mixed with saliva in the oral cavity. Therefore, food bolus formation should be considered to take place from the oral cavity to the pharynx. In previous studies, the chewed food was evaluated after the food had been removed from the oral cavity. However, it has been pointed out that spitting food out of the oral cavity interferes with natural food bolus formation. Therefore, we observed food boluses immediately before swallowing using an endoscope to establish a method to evaluate the food bolus‐forming function, and simultaneously performed endoscopic evaluation of food bolus formation and its relationship with the number of chewing cycles. The subject was inserted the endoscope nasally and instructed to eat two coloured samples of boiled rice simultaneously in two ingestion conditions ('as usual' and 'chewing well'). The condition of the food bolus was graded into three categories for each item of grinding, mixing and aggregation and scored 2, 1 and 0. The score of aggregation was high under both ingestion conditions. The scores of grinding and mixing tended to be higher in subjects with a high number of chewing cycles, and the score of aggregation was high regardless of the number of chewing cycles. It was suggested that food has to be aggregated, even though the number of chewing cycles is low and the food is not ground or mixed for a food bolus to reach the swallowing threshold.